Understanding liver transplantation outcomes through the lens of its tissue-resident immunobiome - Prosser, AC; Klenerman, P; Lucas, M (Lippincott, Williams & Wilkins, 2025)
Tissue-resident lymphocytes (TRLs) provide a front-line immunological defense mechanism uniquely placed to detect perturbations in tissue homeostasis. The heterogeneous TRL population spans the innate to adaptive immune continuum, with roles during normal physiology in homeostatic maintenance, tissue repair, pathogen detection, and rapid mounting of immune responses. TRLs are especially enriched in the liver, with every TRL subset represented, including liver-resident natural killer cells; tissue-resident memory B cells; conventional tissue-resident memory CD8, CD4, and regulatory T cells; and unconventional gamma-delta, natural killer, and mucosal-associated invariant T cells. The importance of donor- and recipient-derived TRLs after transplantation is becoming increasingly recognized, although it has not been examined in detail after liver transplantation. This review summarizes the evidence for the roles of TRLs in liver transplant immunology, focusing on their features, functions, and potential for their harnessing to improve transplant outcomes.